Analisis Pengelolaan Dana Zakat di BAZNAS Kota Bukittinggi - Chindy Hidayatullah; Rika Widianita (Lembaga Yasin AlSys, 2026)
Zakat fund management is an important instrument in promoting community welfare through the economic empowerment of the ummah. Although zakat governance has been widely studied, research that specifically analyzes the processes of collecting, distributing, and the constraints in managing zakat funds at the National Zakat Agency (BAZNAS) of Bukittinggi City remains limited. This study aims to analyze zakat fund management at BAZNAS of Bukittinggi City and identify the constraints encountered in its implementation. This study employed a qualitative approach with a case study design, involving the leaders and administrators of BAZNAS of Bukittinggi City as well as several beneficiaries or mustahik selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The results show that zakat fund management has been implemented through collection and distribution mechanisms that are in accordance with the provisions of Islamic law and the principles of organizational management. However, the optimization of zakat management still faces constraints in the form of low community participation outside the State Civil Apparatus (ASN), the suboptimal use of digital technology, and the dominance of consumptive distribution programs. These findings strengthen the application of George R. Terry’s management theory and the principles of good governance in the management of zakat institutions. The conclusion of this study emphasizes the importance of improving collection strategies, management transparency, service digitalization, and the development of productive zakat programs to increase the effectiveness of zakat management. The implications of the study include theoretical contributions to the development of zakat management studies and practical implications for BAZNAS in strengthening zakat governance that is more transparent, adaptive, and oriented toward the economic empowerment of mustahik.